Dimension Effect on the Ultrasonic Pulse Velocity - Arman, Hasan; Khosravi, Sadieh; Osman, Mawadah Abdullah; Alnaqbi, Fatema Mohamed; AlYammahi, Aishah Abdullah (International Journal of Geography and Geology, 2016)
Ultrasonic pulse velocity test is non-destructive and relatively simple to carry out at both in-situ and laboratory conditions. The sonic velocity (SV) test has been used to determine the dynamic properties of rocks in different applications of rock and geotechnical engineering. In the laboratory conditions, the SV tests determine the velocity of propagation of elastic waves through the rock samples. The velocities of P (Vp) and S (Vs) waves are calculated from the measured travel times and distance between transmitter and receiver. The SV values of rocks are influenced and controlled by different factors such as rock type, density, grain size and shape, etc. This study focuses on the possible dimensional, sample diameter and sample length to sample diameter ratio, effect on the mean Vp, mean dynamic elastic modulus, Ed, mean shear modulus, Gd, mean Poisson’s ratio, υd and mean dry density, ρ. For sample preparation and the SV tests, the representative rock blocks of Upper Eocene-aged limestone, Dammam Formation, is collected from Jabal Hafeet in Al Ain City, United Arab Emirates (UAE) and taken to the laboratory. Forty-nine SV tests was carried out on the prepared core samples having different dimensions. The study reveals that the Vp, Ed, Gd, υd and ρ of limestone can be estimated using the simple linear mathematical equations. Even though the obtained equations are useful and practical, but it still needs better ratification with more samples having different dimensions in order to use confidently in engineering applications.